Developmental nicotine exposure engenders intergenerational downregulation and aberrant posttranslational modification of cardinal epigenetic factors in the frontal cortices, striata, and hippocampi of adolescent mice - Buck, Jordan M. (Epigenetics Chromatin, 2020)
BACKGROUND: Maternal smoking of traditional or electronic cigarettes during pregnancy, which constitutes developmental nicotine exposure (DNE), heightens the risk of neurodevelopmental disorders including ADHD, autism, and schizophrenia in children. Modeling the intergenerationally transmissible impacts of smoking during pregnancy, we previously demonstrated that both the first- and second-generation adolescent offspring of nicotine-exposed female mice exhibit enhanced nicotine preference, hyperactivity and risk-taking behaviors, aberrant rhythmicity of home cage activity, nicotinic acetylcholine receptor and dopamine transporter dysfunction, impaired furin-mediated proBDNF proteolysis, hypocorticosteronemia-related glucocorticoid receptor hypoactivity, and global DNA hypomethylation in the frontal cortices and striata. This ensemble of multigenerational DNE-induced behavioral, neuropharmacological, neurotrophic, neuroendocrine, and DNA methylomic anomalies recapitulates the pathosymptomatology of neurodevelopmental disorders such as ADHD, autism, and schizophrenia. Further probing the epigenetic bases of DNE-induced multigenerational phenotypic aberrations, the present study examined the expression and phosphorylation of key epigenetic factors via an array of immunoblot experiments. RESULTS: Data indicate that DNE confers intergenerational deficits in corticostriatal DNA methyltransferase 3A (DNMT3A) expression accompanied by downregulation of methyl-CpG-binding protein 2 (MeCP2) and histone deacetylase 2 (HDAC2) in the frontal cortices and hippocampi, while the expression of ten-eleven translocase methylcytosine dioxygenase 2 (TET2) is unaltered. Moreover, DNE evokes multigenerational abnormalities in HDAC2 (Ser(394)) but not MeCP2 (Ser(421)) phosphorylation in the frontal cortices, striata, and hippocampi. CONCLUSIONS: In light of the extensive gene regulatory roles of DNMT3A, MeCP2, and HDAC2, the findings of this study that DNE elicits downregulation and aberrant posttranslational modification of these factors in both first- and second-generation DNE mice suggest that epigenetic perturbations may constitute a mechanistic hub for the intergenerational transmission of DNE-induced neurodevelopmental disorder-like phenotypes.